Penerapan Teknologi Informasi dalam Administrasi Pelayanan Kesehatan Rawat Jalan - Yanti Mustafa; Sri Yulianty Mozin (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
The implementation of information technology in outpatient healthcare administration has become a strategic approach to improving service efficiency and quality in healthcare facilities. Administrative processes that are still managed manually often lead to various problems, including long waiting times, data recording errors, and service delays. This study aims to comprehensively review the application of information technology in outpatient healthcare administration based on previous scholarly studies. This research employs a literature review method by examining national and international journal articles, books, and relevant policy documents. Literature searches were conducted through several online databases using specific inclusion criteria and analyzed through thematic analysis and narrative synthesis. The findings indicate that the use of information technology, such as electronic registration systems, electronic medical records, and healthcare management information systems, significantly improves administrative efficiency, data accuracy and integration, and managerial decision-making. Furthermore, information technology contributes to higher patient satisfaction and improved outpatient service performance. However, several challenges remain, particularly related to human resource readiness, infrastructure availability, and data security issues. Therefore, strong policy support, continuous capacity building, and systematic evaluation are required to ensure the optimal implementation of information technology in outpatient healthcare administration.